Daya Hambat Air Perasan Daun Pucuk Merah (Syzygium oleana) Terhadap Pertumbuhan Bakteri Staphylococcus aureus - Dj, Herlinda Djohan; Sugito, Sugito; Sutriswanto, Sutriswanto (Jurnal Laboratorium Khatulistiwa, 2022)
Indonesia is a country that has a fairly high biodiversity, one of which is red shoots (Syzygium oleana). Red shoots are reported to have strong potential to inhibit the growth of bacteria including Staphylococcus aureus because they contain tannins, saponins, flavonoids, and essential oils. To increase effectiveness in exploiting the potential of red shoot leaf extract, it is made in a practical and easy to use dosage form. One of the effective dosage forms for topical therapy is juice. The parameter of this research is the inhibition of red shoot leaf juice (Syzygium oleana) against the growth of Staphylococcus aureus bacteria. This research is a quasi-experimental research (Quasy Experiment). The sample in this study was red shoots leaf juice with 6 repetitions, the number of samples was 24, diluted from the red shoots leaf extract to 5%, the average inhibition zone was 7,33,33 mm, 10% inhibition zone 8 ,17,33 mm, 15% inhibition zone 9 mm and 20% inhibition zone 11.4 mm, amoxicillin positive control and negative control using aquadest. Based on the statistical results of the Anova test, the value of Sig. 0.000 (p= 0.001 < 0.005) which means that there is an effect of red shoot leaf juice (Syzygium oleana) in inhibiting the growth of Staphylococcus aureus by diffusion method.